2022
DOI: 10.3389/fendo.2022.1023919
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipoprotein (a) associates with the risk of renal function damage in the CHCN-BTH Study: Cross-sectional and Mendelian randomization analyses

Abstract: BackgroundEvidence regarding the effects of lipoprotein (a) [lp(a)] and renal function remains unclear. The present study aimed to explore the causal association of serum lp(a) with renal function damage in Chinese general adults.MethodsA total of 25343 individuals with available lp(a) data were selected from the baseline survey of the Cohort Study on Chronic Disease of Communities Natural Population in Beijing, Tianjin, and Hebei (CHCN-BTH). Five renal function indexes [estimated glomerular filtration rate (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This hypothesis is supported by a prior analysis of the Cohort Study on Chronic Disease of Communities Natural Population in Beijing, Tianjin, and Hebei study. 41 In this analysis, higher Lp(a) mass concentration was associated with lower eGFR in a cross-sectional analysis. However, higher genetically predicted Lp(a) was associated with higher eGFR in a Mendelian randomization analysis conducted in the same study population, suggesting that Lp(a) may not cause low kidney function.…”
Section: Discussionmentioning
confidence: 65%
“…This hypothesis is supported by a prior analysis of the Cohort Study on Chronic Disease of Communities Natural Population in Beijing, Tianjin, and Hebei study. 41 In this analysis, higher Lp(a) mass concentration was associated with lower eGFR in a cross-sectional analysis. However, higher genetically predicted Lp(a) was associated with higher eGFR in a Mendelian randomization analysis conducted in the same study population, suggesting that Lp(a) may not cause low kidney function.…”
Section: Discussionmentioning
confidence: 65%
“… 11 In our study, tafolecimab treatment reduced the Lp(a) levels in Chinese hypercholesterolemia and a significant correlation was observed between reductions in Lp(a) and LDL-C, consistent with the findings of evolocumab. 24 Given the lower Lp(a) levels in Chinese population and skewed distribution of Lp(a) levels, together with elevations of Lp(a) levels observed in placebo group which was possibly due to the use of statins and concomitant chronic kidney disease of enrolled patients, 25 , 26 the potential Lp(a) lowering effects of tafolecimab still warrant further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…On one hand, the kidney is thought to be a site of Lp(a) catabolism, and pathological alterations in the kidney, such as those occurring in end-stage renal disease, might lead to decreased excretion of Lp(a) and thus increased Lp(a) levels [ 30 ]. A study involving a large sample of Chinese adults found that Lp(a) levels were independently associated with several renal function indicators, including estimated glomerular filtration rate (eGFR), serum creatinine (Scr), and blood urea nitrogen (BUN) [ 31 ]. However, the relationship between renal function and Lp(a) levels is a subject of ongoing debate, with some studies reporting conflicting results [ 32 ].…”
Section: Discussionmentioning
confidence: 99%